Biogeographical affinities of fish associated to the shrimp trawl fishery in the Gulf of Tehuantepec, Mexico - Martínez-Muñoz, Marco Antonio (2016)
Fish by-catch of shrimp fishery from the Gulf of Tehuantepec is composed of several species that are mainly discarded. In this study, fish by-catch species composition, distribution and biogeographical affinities were analyzed. For this, a total of 15 cruises were carried out on the continental shelf, at depths from 15 to 64 m, during 2003, 2004, 2005 and 2013. Results showed that fish by-catch was represented by 58 families, 129 genera and 242 species. The families Haemulidae, Sciaenidae, Paralichthyidae, Gerreidae and Carangidae accounted for > 70 % of the catch. Haemulopsis axillaris, Syacium ovale, Selene peruviana, Diapterus peruvianus, Larimus acclivins and Stellifer erycimba were the most frequent species at < 40 m depth (inner shelf), and Prionotus stephanophrys, Scorpaena russula, Porichthys analis and Synodus scituliceps were dominant at 40-60 m depth (outer shelf). Analysis of biogeographical affinities showed that 36.1 % of species had a wide distribution, from San Diego Province to the Panamic Province, while 13.2 % had a restricted distribution in the Mexican and Panamic Provinces. The ichthyofaunal composition was markedly influenced by the local environment and seasonal conditions.